Lymphocyte Proliferation Activity MTT -Test of Ethanolic Extract of Pasak Bumi Root (Eurycoma longifolia Jack) on Induced 7,12-Dimethylbenz[A] Antracene (DMBA) Female Sprague Dawley Rat - Falah, Lily Noor; Yuliani, Sapto (Indonesian Journal of Cancer Chemoprevention, 2011)
Pasak bumi root (Eurycoma longifolia Jack) contains quasinoid. Quasinoid potentially hasÃÂ  antitumor/anticancer,ÃÂ  anti-parasitic,ÃÂ  andÃÂ  immunostimulatoryÃÂ  activity.ÃÂ  TheÃÂ  aimÃÂ  ofÃÂ  this research was to study the lymphocyte proliferationÃÂ  activity MTT-testÃÂ ÃÂ  of ethanol extract ofÃÂ  EurycomaÃÂ  longifoliaÃÂ  JackÃÂ  rootÃÂ  onÃÂ  inducedÃÂ  byÃÂ  7,12-dimethylbenz[a]ÃÂ  antraceneÃÂ  (DMBA) female Sprague Dawley rat. The test was done at 6 groups of 10ÃÂ  SD rat each. Each groups wasÃÂ  administeredÃÂ  orallyÃÂ  withÃÂ  DMBAÃÂ  (GroupÃÂ  I)ÃÂ ÃÂ ÃÂ  doseÃÂ  ofÃÂ  20 mg/kgÃÂ  bw,ÃÂ  corn oilÃÂ  (GroupÃÂ  II), baseline (Group III), andÃÂ  ethanol extract of pasak bumi root dose 12.6; 25.2; and 50.4 mg/kg bw (Group IV,V,and VI). Ethanol extract is given for 5 weeks. At the second week five rats wereÃÂ  sacrificedÃÂ  toÃÂ  isolateÃÂ  theÃÂ  lymphocytesÃÂ  ofÃÂ  spleenÃÂ  thenÃÂ  ratsÃÂ  areÃÂ  injectedÃÂ  orallyÃÂ  with DMBA 2 times a week for 5 weeks. At the eight until twenty fourth week all groups were justÃÂ  administeredÃÂ  byÃÂ  aquades.ÃÂ  MeasurementÃÂ  ofÃÂ  spleenÃÂ  relativeÃÂ  weightÃÂ  andÃÂ  isolationÃÂ  ofÃÂ  the lymphocyteÃÂ  spleenÃÂ  wereÃÂ  doneÃÂ  atÃÂ  secondÃÂ  weekÃÂ  andÃÂ  theÃÂ  lastÃÂ  ofÃÂ  experiment.ÃÂ  Lymphocyte proliferationÃÂ  activityÃÂ  wereÃÂ  measuredÃÂ  byÃÂ  MTT-reductionÃÂ  method.ÃÂ  DataÃÂ  wereÃÂ  analyzed statisticallyÃÂ  byÃÂ  analyzesÃÂ  ofÃÂ  varianceÃÂ  (anova)ÃÂ  continuedÃÂ  byÃÂ ÃÂ ÃÂ ÃÂ ÃÂ  LSDÃÂ  testÃÂ  andÃÂ  KruskallÃÂ  Wallis continued by Mann Whitney test. The result showed that limphocyte proliferation activity MTT of ethanol extract of E. longifolia root doses of 12.6; 25.2; and 50.4 mg/kg bw for 14 days prior to DMBA-induced areÃÂ  339.35 ÃÂ± 8.43;61.20 ÃÂ± 6.27;ÃÂ  310.28 ÃÂ±ÃÂ  6.81ÃÂ ÃÂ  andÃÂ  dose 50,4 mg/kg bw afterÃÂ  DMBA-induced is 122.108 ÃÂ±ÃÂ  11.426